New insights in to ancient resistance: the molecular side of cell wall appositions - Greenshields, David; Liu, Guosheng; Selvaraj, Gopalan; Wei, Yangdou (Phytoprotection, 2004)
AbstractThe epidermis lies at the interface between a plant and its environment. As such, the epidermis is crucial for protecting the plant against environmental insults. We focus primarily on cell wall reinforcement-mediated penetration resistance (papilla-resistance) against fungal pathogen attack. The epidermal cell layer of cereal leaves is the only tissue interacting with the powdery mildew fungus, Blumeria graminis, and papilla formation at sites of fungal penetration attempts provides a basal resistance, hampering fungal invasion irrespective of host specific compatibility or incompatibility. To elucidate the genetic scaffolding of penetration resistance mechanisms, we constructed a cDNA library from wheat leaf epidermis at 24-48 h post inoculation with B. graminis f. sp. tritici. We have sequenced 3,000 expressed sequence tags (ESTs) from this cDNA library. EST analysis revealed a large proportion of genes involved in plant defense/stress responses (1/3) and a low frequency of “house-keeping” genes. Enrichment of defense genes from this EST collection has allowed us to identify several defense and signaling pathways that have been hitherto poorly characterized, including cell wall biosynthesis, vesicle trafficking, redox regulation and metal homeostasis. Our results suggest that a global analysis of transcripts from this epidermis-specific cDNA library makes it feasible to define a full set of genes involved in early plant resistance associated with cell wall modifications.